Optimizations of Digital Marketing in Increasing Competitive Advantage: Case Study of Elzatta Hijab Garut - Mulia, Hari; Safitri, Ajeng Erna (Golden Ratio of Data in Summary, 2024)
Business competition in the hijab industry is getting tighter with the development of digital technology that changes marketing patterns and consumer behaviour. Digital marketing is one of the main strategies that companies can use to increase competitiveness and expand market reach. This study aims to analyse the effect of digital marketing on competitive advantage at Elzatta Hijab Garut. This research uses a quantitative approach with descriptive and associative methods. The population in this study were Elzatta Hijab Garut customers, with a sample size of 68 respondents selected using purposive sampling technique. Data collection techniques were carried out through questionnaires, and data analysis using simple correlation and regression techniques. The results showed that digital marketing plays a role in increasing competitive advantage, especially through social media and e-commerce-based marketing strategies. However, it was found that digital marketing is not the only factor that determines the company's competitiveness. Other factors such as product quality, price, customer service, and business innovation also contribute to maintaining a competitive advantage in the market. The implication of this research shows that Elzatta Hijab Garut needs to optimise its digital marketing strategy by increasing customer interaction on digital platforms, better managing customer data, and strengthening promotional strategies to remain competitive in the competitive hijab industry.